2016
DOI: 10.1093/ndt/gfw090
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum vitamin B12 and folate with mortality in incident hemodialysis patients

Abstract: A B S T R A C TBackground: Vitamin B12 (B12) and folate are essential vitamins that play important roles in physiological processes. In the general population, many studies have evaluated the association of these vitamins with clinical outcomes, yet this association in hemodialysis (HD) patients remains unclear. Methods: We examined the association of serum folate and B12 with mortality in a 5-year cohort of 9517 (folate) and 12 968 (B12) HD patients using Cox models with hierarchical adjustment for sociodemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 23 publications
1
43
1
1
Order By: Relevance
“…11 Another strength of this study is the implementation of a robust method of plasma concentration of vitamin B 12 quantification. The accuracy of the assay that we used has been evaluated using the vitamin B 12 World Health Organization International Standard. 33 Moreover, it has been reported that the Elecsys Vitamin B 12 assay is not affected by anti-intrinsic factor antibodies, enhancing the reliability of this assay.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 4 more Smart Citations
“…11 Another strength of this study is the implementation of a robust method of plasma concentration of vitamin B 12 quantification. The accuracy of the assay that we used has been evaluated using the vitamin B 12 World Health Organization International Standard. 33 Moreover, it has been reported that the Elecsys Vitamin B 12 assay is not affected by anti-intrinsic factor antibodies, enhancing the reliability of this assay.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Vitamin B 12 is a hydrosoluble vitamin that plays a substantial role in 1-carbon metabolism. The 1-carbon pathway is involved in several biological functions beyond fetal development, such as mitochondrial metabolism, immune response, and nucleotide homeostasis in nonproliferative tissues.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations